Epidemiological investigation into the source of water contamination at a tertiary care cancer hospital - Kumar, Atul; H., Vikas; Satpathy, Sidhartha; Hakim, Abdul (International Journal of Research in Medical Sciences, 2018)
Background: Water quality impacts the performance of the hospitals and leads to drastic health service deterioration affecting infection control programs, along with safety of the patients and staff. Good quality water is an essential prerequisite to ensure optimal patient care, and the well-being of the staff and visitors in a hospital environment. Objectives was to study the current water supply and treatment system in the cancer hospital. Also, to carryout root cause analysis of the causes of episodes of diarrhoea amongst patients and staff and to identify the source of infection and suggest improvement in the existing system to prevent recurrence. Methods: There were 25 reported cases of diarrhoea and other gastrointestinal symptoms between May 12 and June 2 2017, allegedly due to water contamination occurring in admitted patients and staff of a tertiary care cancer hospital in north India. This was reported to Hospital Administration, which prompted an epidemiological investigation. Results: Formation of Biofilms on the plastic taps was found to be the main reason for contamination of water. Conclusions: It was very clear that deposition of biofilm within the plastic taps was the main reason of diarrhea among the patients.